A comparison of US judicial and NAFTA panel review of trade remedy cases. (14th July 2008) - Colares, Juscelino F.; Bohn, John W.
Empirical analysis of NAFTA Chapter 19 panel decisions shows that they are far more likely than US courts to overturn US agency decisions despite being bound to apply the same law under the same standard and principles of review that US courts adopt. Also, Chapter 19 panels have produced outcomes more favourable to Canadian importers than have US courts. This outcome illustrates that the facial legal terms of an international agreement may give a misleading impression of how it will actually be implemented, and suggests that greater attention must be paid to how it will be interpreted and by whom.